Urban Health Advantages and Penalties in India : Overview and Case Studies - Mullen, Patrick; Nair, Divya; Nigam, Jayati; Seth, Katyayni (World Bank, Washington, DC, 2016)
It is increasingly recognized that India is urbanizing rapidly, that urbanization is accompanying and contributing to economic growth, but that living conditions in urban areas are often not adequate, particularly for the poor. Health, nutrition, and population conditions are an important part of the urbanization equation. This paper explores the extent to which health, nutrition, and population conditions may be contributing to the benefits of urbanization, as well as the extent to which they may reflect its costs. This is an exploratory study that reviews available information on health, nutrition, and population conditions in urban India. Recognizing that national generalizations and statistics may mask considerable diversity in how the opportunities and challenges of urbanization and health are met in different cities across the country, this paper also draws on specifics of four case studies: Chennai in Tamil Nadu, Bhubaneswar in Odisha, Meerut in Uttar Pradesh, and Shillong in Meghalaya. The summary section provides an overview of this exploratory analysis, discussing the patterns and issues that emerge, along with policy implications in section one. This introductory section two briefly discusses how urbanization and health may be conceptualized, and describes the methodology of this paper. Section three describes governance and organization of urban health systems. Sections four and five review data on the demographic and epidemiological situation in urban India, as well as service utilization. Section six analyzes disparities in health outcomes and access to services, and section seven focuses on water supply and sanitation in urban areas.